Sei sulla pagina 1di 4

Space Technology, Section-A, Module -3, Lecture-3

Note: The optimization problem may be restated as maximization of function (ratio of

payload to total vehicle weight)

M

L

M

01

=

mission)

V

rocket, n

.

Where

n

∆=

VU

rocket n

,

ei

1

ln

1 +

λ

i

ε λ

i

+

i

=

This leads to same optimal value of

n

1

λ

i

U

ei

n

i

= 1

ln

(

λ , subject to a prescribed

i

1

+

λ

i

µ

i

)

becomes the constraint on

λ

i

Example: (for Case I) Suppose if Ue and ε is same for all stages.

ln   M   =

L

M

01

n

1

ln

λ

i

1 +

λ

i

=

n

1

F (

λ

i

)

(Objective function)

V

rocket n

,

U

e

=

n

1

ln

1 +

λ

i

ε λ

+

i

=

n

1

i

G

(

λ

i

)

(Constraint function)

LGλ = λαλ+ F

()

()

ii

()

i

F

1

×

(1 +

λ λ

i

)

i

λ

i

λ

i

1 +

λ

i

(1

+

λ

i

)

2

=

,

G

1

=

λ

i

1 +

λ

i

ε λ

+

i

 

×

(

ε λ

+

i

)

(1 +

λ

i

)

(

ε λ

+

i

)

2

ε+λ + α

i

ελ - α

i

λ = 0

i

or

λ

=

i

 

ε

 

αε

 

1

 

=

or

α

=

 

α

′− 1

εα

1

α ε

α

Since all other terms are constant λ should be a constant,

i

M

L

M

01

=

n

1

λ

1 +

λ

=    

λ

1 + λ

n

Which is same as optimization based on maximum V .

n

(by the

Case II. Suppose if U altered

e is constant for all the stages, but

(

+

ε α

i

1)

λ αε

i

+

λ

i

=

αε

i

1

α ε

i

i

=

0

ε i is varied, equation (6) could be

and

M

L

M

01

=

n

1

αε

i

+

ε α

i

1

αε

i

=

n

1

αε

i

(

ε

i

)(

1 α

1

)

(8)

(9)

For known

M L

M

01

and

ε i , the Lagrange multiplier α could be evaluated from equation (9).

Upon back substitution in equation (8) one can get λ i

Example: for a two stage rocket

αε 1 αε α 2 εε M L 2 1 2 = = M ε
αε
1 αε
α 2 εε
M L
2
1
2
=
=
M
ε
1)(
α
1)(
ε
1)(
α
1)
( α
1)(
2
1)(
ε
1)
ε
01 (
1
2
1
2
α
(
ε
1
)(
ε
1
)
M L
1
2
=
(
α
1
)
M
εε
01
1
2
M
αε
M
αε
02
1
L
2
=
and
=
λ
=
λ 1 =
(
2
− M
1 α
ε
1 )
M
− M
(
1 α
ε
)
M 01
02
02
L
2
M
ε
α
ε
α
M L
02
1
2
or
=
and
=
M
(
ε
1)(
α
1)
M
(
ε
1)(
α −
1)
01
1
02
2
ε ε
(
− 1)
1
2
M
M
02 =
01 M
L
ε ε
(
− 1)
2
1
Note:
If
ε 1 =0.1
&
ε 2 =0.2
M
= 0.66
M
M
ε <ε
<
M
M
02
01
L
1
2
M 02
01
L
If
ε 1 =0.2
&
ε 2 =0.1
M
= 1.51
M
M
ε <ε
>
M
M
02
01
L
2
1
M 02
01
L

It can be observed from the above result that, if the structural co-efficient of higher

stage(ε 2 ) is greater than the lower stage(ε 1 ), the mass of that higher stage is less than

the mass of that same stage when the structural co-efficient is constant (Case 1

condition), similarly if the structural co-efficient of lower stage(ε 1 ) is higher than the

higher stage(ε 2 ), the mass of the higher stage will be higher than the mass of that same

stage when the structural co-efficient is constant (case 1 condition).

Case III

If the exhaust velocity followed.

V

n

=

n

U

i = 1

ei

U

e

ln

is also allowed to be varied, similar procedure could be


1 +

λ

i

ε

i

+ λ

i


=

n

i = 1

F (

U ei

,

ε λ

i

i

)

(10)

This objective function has to be maximized subjected to the constraint

M

L

M

01

=

n

1

λ

i

1 λ

+

i

Expressing the constraint function in log form

ln

M

L

M

01

=

n

1

ln

λ

i

1 +

λ

i

=

n

1

G (

ε λ

i

,

i

)

The maximum condition is when λ i satisfies

λ

i

U

ei

ln

1 +

λ

i

ε

i

+

λ

i

 

 

After differentiation rearrangement

λ

i

=

α

U

ei

ε

i

1

α

U

ei

ε

i

+

α

λ

i

ln

λ

i

1

+

λ

i

)

 = 0

(11)

(12)

(13)

(14)

Now ‘α’ can be obtained by substituting (14) in (11) i.e.

Knowing ‘α’, individual payload ratios, λ can be obtained from (14)

i

Example: for a two stage rocket

M

L

M

M

01

02

M

01

M

=

=

 

(

( ε α 1 U

ε α

1

U

e

1

)

(

( ε α 2 U

ε α

2

U

e

2

)

(

ε

1

1

)(

)( α U

α

U

e

1

1

) (

ε

2

1)(

1 )( α U

α

U

e

2

1)

ε

1

(

( α U e 1

α

U

e 1

)

( ε

1

1

) ((

( ε − 1 − 1 ) (( α U e 1 ) 1 )

α

U

e 1

)

1)

 

ε

1

(

ε

2

1) U

e

2

M

M

ε 2 ( ε 1 − 1) U e 1 01 L

ε

2

(

ε

1

1) U

e

1

01

L

and

when

02( approx )

If ε 1 = ε 2 , U e 2 ≈ M , M 02
If ε 1 = ε 2 ,
U
e
2
M
,
M 02
01 M
L
U
e 1
> U
,
M
M
U e 2
e 1
02 >
01 M
L

M

L

M

02

α

U

e

ε

2 ( α

M U e 2 e 1 02 > 01 M L M L M 02 α

U e 12

)

= ( ε

2

1 ) ((

L M 02 α U e ε 2 ( α U e 12 ) = (

α

U e 2

)

1)

<< 1

It can be observed from the above equation that if the incremental velocity of higher

stage (U e2 ) is greater than that of lower stage (U e1 ), the

be higher than the mass of the same stage when the incremental velocity and the structural co-efficient are constant.

mass of that higher stage will

Further reading

1. Mech. & Thermodynamics of Propulsion (2 nd Ed.) by Hill & Peterson. (Appendix VIII)